Facebook Digital Marketing: A Thematic Analysis of the Practice of Public Relations Models of Star-Rated Hotels in Bandung - Sanjaya, Santosa (Jurnal Riset Bisnis dan Investasi, 2020)
The purpose of this study is to uncover the Grunig’s Public Relations models applied by star-hotels in Bandung through their promotion on Facebook. The thematic analysis was used in this study. The sample included 50 star-hotels in Bandung. All reviews from hotel occupants were checked and coded according to the concerns referred to hotel occupants. All hotels surveyed showed one-way and two-way communication models. For the one-way communication model, some hotels applied press agent/publicity. However, all hotels showed an effort towards the public information model as they disseminated complete information. For the two-way communication model, some hotels applied the two-way asymmetrical model. They responded to criticism from hotel residents but did not reply directly to the problems. Finally, some hotels applied the two-way symmetrical model because they responded directly to complaints against hotel occupants. Keywords – Facebook digital marketing, 5 Star-hotels, one-way communication model, Two-way communication model